FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE TERHADAP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Tampubolon, Anita Octrani; Iskak, Jamaludin (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to empirically prove the effect of operating cash flow, leverage, liquidity and firm size on financial performance in manufacturing companies that are officially listed on the Indonesia Stock Exchange (IDX) in the period 2018-2020. Based on the criteria that have been set, 71 manufacturing companies have been selected as samples for this research using a purposive sampling method. The method of analysis used in this study is multiple linear regression using EViews version 12 and Microsoft Excel 2016. The results obtained from this study indicate that ther effect of leverage is a positive and significant on financial performance, while operating cash flow and liquidity have a positive and significant effect. not significant on financial performance and variable firm size has a negative and insignificant effect on financial performance.